Bilateral Warthin tumor in psoriatic patients in therapy with multiple immunosuppressive therapy. (March 2015) - Burlando, M; Cozzani, E; Chinazzo, C; larosa, M; Boggio, M; Parodi, A
Anti-TNFα drugs have strongly changed the way in which we deal with moderate and severe psoriasis. However, it is debatable whether biological drugs could increase the risk of developing cancer. The correlation between anti-TNFα drugs and lymphomas is well-known and is reported in all the technical details of biologic drugs. However, the association between anti-TNFα agents and solid tumors is still controversial. The authors report a case of bilateral salivary gland tumor in a psoriatic patient treated with several immunosuppressive therapies including anti-TNFα inhibitors.